Paying your fair share: Perceived fairness and tax compliance - Nathan, Brad; Perez-Truglia, Ricardo; Zentner, Alejandro (Journal of Accounting and Economics, 2026)
We provide evidence on the role of perceived fairness in tax compliance. Are households more willing to pay taxes when they believe others contribute their fair share? We investigate this question with a natural field experiment in the context of U.S. property taxes. Using an information-disclosure experiment, we exogenously shifted households’ perceptions of the average tax rate paid by others. We find that higher perceived average tax rates increase perceptions of fairness and reduce the likelihood of tax appeals. Quantifying the effect, for every additional $1 paid by the average household, a taxpayer is willing to contribute $0.43 more. In the field experiment, subjects were informed about the average tax rate but not why it might differ from theirs. A complementary survey shows this context matters: when households learn others pay lower rates due to exemptions such as disability or advanced age, they are more willing to tolerate unequal rates.